Colon polyp in a 6-year-old girl - Oronoz, Luis A.; Gutiérrez Galiana, Horacio; Schneeberger, Federico; Cardeza, Hector (Cirugía del Uruguay, 1978)
Report on a polyp a six-year-old child, which we believe to be the first such case in national literature. The paper contains a brief review of its frequency, symptomatology, pathology, diagnosis and treatment . Author remarks on the non-malignant nature of polyp and on possibility of endoscopic treatment.